2022
DOI: 10.17509/ajse.v2i3.39425
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization of II-VI Thin Films for Solar Cells Application

Abstract: Cds and CdTe both are effective absorber semiconductors for thin-film solar cells. It is a naturally n-type material, which has a direct bandgap value of 2.42 eV at room temperature It has great importance in light detectors in this work, CdS thin films (TF) were synthesized on glass substrates by RF Magnetron sputtering technique in an inert gas atmosphere. The electrical properties of CdS were characterized by the Van Der Pauw method. The films showed p-type conductivity, while the films deposited at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The bulk concentration of the Thin film value was observed to be of the order . This was in agreement with previous work of [5]. The annealed thin film had a resistivity value of , while the annealed and etched thin film had a resistivity value of , according to Table 2.…”
Section: Electrical Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…The bulk concentration of the Thin film value was observed to be of the order . This was in agreement with previous work of [5]. The annealed thin film had a resistivity value of , while the annealed and etched thin film had a resistivity value of , according to Table 2.…”
Section: Electrical Propertiessupporting
confidence: 92%
“…Faraj, Eisa, & Pakhuruddin [17] also reported that the nearer resistivity value for film by Spray Pyrolysis technique. The films deposited have the conductivity value about which are in good agreement with the previous report of [5]. The prepared thin film has conductivity [18].…”
Section: Electrical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Although silicon SCs are highly efficient, they require a substantial infrastructure to manufacture and must be produced in a highly hygienic environment due to the reaction involved, as well as significant energy cost. Thus, many researchers have been investigating various other semiconductors for potential use in SCs, which offer a promising avenue for sustainable energy production. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, PV technology (Ahmad et al, 2022) is indispensable and used as a source of electricity to supply demands. Therefore, it is crucial to increase the tracking maximum power point (MPP) and drag the highest power available from the PV panel without being affected by changes in light during the day.…”
Section: Introductionmentioning
confidence: 99%